Controversy around the morphea - Dańczak-Pazdrowska, Aleksandra; Cieplewicz, Paulina; Żaba, Ryszard; Adamski, Zygmunt; Polańska, Adriana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Morphea, also known as localized scleroderma, is a chronic, autoimmune disease of connective tissue. It is characterized by a typical clinical feature. In morphea, there is no Raynaud’s phenomenon, no sclerodactyly or no ulcerations on the fingertips. Although morphea and systemic sclerosis have been perceived as separate disease entities for years, they are still confused both by patients (which is a source of unnecessary stress) and doctors. This may be due to, in part, misunderstood terminology. The controversy around morphea also concerns the division of this disease entity, including its less common subtypes, such as eosinophilic fasciitis. Discussions also revolve around the diagnostic aspects and possible treatment options. The paper attempts to present the debatable aspects regarding nomenclature, classification, diagnosis and treatment of morphea.